Penggunaan Teknologi Berbasis RFID untuk Security System di Perpustakaan IAIN Kediri - Muhamad Hamim (IJAL (Indonesian Journal of Academic Librarianship), 2018)
The basis of the research is an indication that there are many library collections that are not found on the shelves but are listed in the database. The lost of this collections may be due to the release of the library collection without going through the prescribed procedures. So it needs to be built a security system that is integrated with the library database to protect library collections. RFID is a wireless cable-based communication technology that allows users to be able to identify an object by a chip / tag using a special reader. RFID can be used as an alternative to library system security devices to protect library collections. One of the advantages of RFID technology is the ability to scan objects that are not attached to an RFID reader. RFID can scan objects that have tags attached even if they are blocked by other objects. RFID technology is very likely to be applied in libraries and integrated with library software based on the assumption that RFID has been used in the retail sector, the process is almost the same as the system in the library. In addition, open source library software is very likely to be developed to support RFID-based security systems. This is because the data stored in RFID tags is text-based characters that can be stored in the database.